Regulation of hydrogenase in Rhizobium japonicum: analysis of mutants altered in regulation by carbon substrates and oxygen. - Merberg, D (1983)
The synthesis of the H2 uptake system in free-living Rhizobium japonicum SR is repressed both by oxygen and by carbon substrates. Mutants selected for the ability to express hydrogenase in 10.0% partial pressure O2 were also less sensitive than the wild type to repression by carbon substrates such as arabinose, glycerol, gluconate, and succinate. The H2 uptake system in another class of mutants, previously shown to be hypersensitive to repression by O2, is also more sensitive to repression by carbon substrates. The oxygen- and carbon-insensitive mutants express the hydrogen uptake system during heterotrophic growth in the absence of hydrogen and thus can be considered constitutive (Hupc). The amount of cytochromes in the Hupc mutants is similar to that in the wild-type strain; however, the Hupc mutants contain greater methylene blue-dependent and O2-dependent hydrogenase activity, both as free-living cells and as bacteroids. Two-dimensional polyacrylamide gel electrophoresis revealed that during heterotrophic growth the Hupc mutant strain SR470 synthesized at least six peptides not found in the wild-type strain. The concentrations of cyclic AMP and guanosine tetraphosphate were similar in strain SR and the Hupc mutants during heterotrophic growth.